Specification and Development of New Pre-College Tests: BET and TEL - Chizmar, John F.; Soper, John C. (American Economic Review, 1981)
The Basic Economics Test (BET) (see Chizmar, Ronald Halinski, and Bernard McCarney) and the Test of Economic Literacy (TEL) (Soper, 1978) are achievement tests of the basic principles of economics designed for use in grades 4 through 6 and in grades 11 and 12, respectively. The BET represents a substantive revision of the Test of Elementary Economics (TEE) developed in 1971, while the TEL is an update of the Test of Economic Understanding (TEU) published in 1963. The decision to revise the TEU and subsequently the TEE was motivated by three considerations. First, the Framework for Teaching Economics: Basic Concepts (W. Lee Hansen et al.) was released in 1977. This document presented the most recent statement of the conceptual structure of the economics discipline and related that structure to decisionmaking. It was envisioned that this structure would be used by curriculum planning groups in designing K-12 economics programs. In conjunction, new evaluation instruments to be used in the planning and evaluation processes reflecting the specifications of the Master Curriculum Guide (MCG) Framework were now needed. Second, the period of the late 1970's saw many important curriculum materials developments. Two deserve special mention. The MCG Strategies for Teaching Economics, available now in five grade-specific or discipline-specific volumes, have detailed specific guidelines for teaching the concepts outlined in the MCG Framework. In addition, a number of excellent audio-visual curriculum products have become available for use at various grade levels (see Laurence Moss). For example, Trade Offs, a series of fifteen 20-minute color television film programs in economics education for children 9 to 13 years of age, was released in 1978. Because of these and other curriculum developments, new testing instruments were now needed. Third, in the decade of the 1970's many theoretical and empirical advances have been made in the models used to evaluate changes in cognitive achievement due to educational innovation (see John Siegfried and Rendigs Fels). Although these models have been devised and utilized primarily at the college level, they have begun to trickle down to evaluations conducted at the high school and grade school levels. Worthwhile evaluation must be built on a solid foundation of good data. In 1970, Wassily Leontief -in his presidential address to the Association cautioned the discipline against elaborate model building (what Frisch called playometrics) in the face of deficient data: